2018
DOI: 10.1186/s12936-018-2370-x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment with artemether–lumefantrine or amodiaquine–artesunate for uncomplicated malaria in children in Sierra Leone: a randomized trial

Abstract: BackgroundPrompt, effective treatment of confirmed malaria cases with artemisinin-based combination therapy (ACT) is a cornerstone of malaria control. Maximizing adherence to ACT medicines is key to ensuring treatment effectiveness.MethodsThis open-label, randomized trial evaluated caregiver adherence to co-formulated artemether–lumefantrine (AL) and fixed-dose amodiaquine–artesunate (AQAS) in Sierra Leone. Children aged 6–59 months diagnosed with malaria were recruited from two public clinics, randomized to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
(83 reference statements)
0
22
0
Order By: Relevance
“…The current study found that CHWs played an important role in ensuring completion of treatment for malaria. The method of measuring complete-treatment in this study satisfies the conditions of being called 'definite adherence' [28,29]. This is another aspect where CHWs offered a big advantage over other providers.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that CHWs played an important role in ensuring completion of treatment for malaria. The method of measuring complete-treatment in this study satisfies the conditions of being called 'definite adherence' [28,29]. This is another aspect where CHWs offered a big advantage over other providers.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that CHWs played an important role in ensuring completion of treatment for malaria. The method of measuring complete-treatment in this study satis es the conditions of being called 'de nite adherence' [28,29]. This is another aspect where CHWs offered a big advantage over other providers.…”
Section: Discussionmentioning
confidence: 99%
“…The “day-4” parasitaemia measure was considered a surveillance tool for artemisinin tolerance, guaranteeing the current WHO-recommended cut-off value (72 hours). 3 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…2 In this fight there is a vast and efficient therapeutic arsenal, however, despite the proven efficacy treatment failures are frequent and may be the result of drug resistance or inadequate exposure to drugs, whether due to failure in prescription and dispensing, incorrect dosage and even if the patient does not adhere to the treatment. 2 , 3 Moreover, resistance to antimalarial chemotherapy has been one of the major obstacle in the fight against this disease. The monitoring of the effectiveness of antimalarial drugs is a crucial component in the disease’s control, as the parasite develops mechanisms to avoid the action of antimalarial compounds.…”
mentioning
confidence: 99%